2021
DOI: 10.6026/97320630017599
|View full text |Cite
|
Sign up to set email alerts
|

Data on self-medication among healthcare students at Najran University, KSA

Abstract: The prevalence of self-medication (SM) has increased in health professionals due to awareness of disease and symptoms. Incorrect use of medication caused harmful effects. To assess the knowledge, attitude and practice of health professionals, this survey was conducted. A cross-sectional study was carried out among health professionals of different specialities. Knowledge, attitude and practice-based questions were asked through an electronically distributed questionnaire. Data were statistically tested using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…Numerous studies have documented this practice among undergraduates, both in the medical and non-medical fields [12,13] as well as among the general populace in other nations including Brazil [14], Peru [15], and KSA [1]. It was identified that health science students around the world are increasingly turning to self-medication [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented this practice among undergraduates, both in the medical and non-medical fields [12,13] as well as among the general populace in other nations including Brazil [14], Peru [15], and KSA [1]. It was identified that health science students around the world are increasingly turning to self-medication [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde bu konuda farklı katılımcı gruplarına yönelik yapılan çalışmalara da kendi kendine ilaç kullanma oranlarının oldukça yüksek olduğu görülmektedir 3,4,9,10,13,16,[24][25][26][27] kendilerine ilaç kullandıkları belirlenirken, lise mezunu hemşirelerin anlamlı olarak daha az ilaç önerdikleri görülmüştür. Kırılmaz tarafından yapılan çalışma sonucunda, lisansüstü düzeyde eğitim alan bireylerin kendi kendilerine ilaç kullanım durumlarının daha fazla olduğu ve eğitim düzeylerinin arttıkça ilaç kullanımlarının da arttığı sonucuna ulaşmıştır.…”
Section: Discussionunclassified
“…Khan et al (6) realizaron una investigación con el fin de mostrar datos de automedicación en estudiantes del área de la salud, donde participaron estudiantes de medicina, odontología, farmacia, enfermería y fisioterapia. La prevalencia de automedicación entre los participantes fue significativamente alta.…”
Section: Introductionunclassified